2018
DOI: 10.1111/bjd.16182
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting quality of life in patients with vitiligo: a nationwide study

Abstract: SummaryIn vitiligo, areas of skin lose their colour and become completely white. These white areas, which are often irregular like islands on a map, usually stand out against the normal skin around them, and are very obvious in individuals with a naturally pigmented (brown or black) skin, or in white-skinned people with a tan. People with vitiligo can become very embarrassed and withdrawn, not wanting to go out or to meet people; as a result, the quality of their day-to-day life can suffer. Vitiligo affects be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
3
16
0
1
Order By: Relevance
“…Our results suggested that AA could affect patients' QOL more than vitiligo or androgenetic alopecia, compared with the previous studies using the similar study protocol in Korea (Bae et al, 2018;Han et al, 2012). More patients with AA have impaired QOL than patients with vitiligo (symptoms: 30.3% vs. 14.6%, functioning: 71.3% vs. 48.8%, and emotions: 81.7% vs. 65.0%) (Bae et al, 2018). For hairspecific Skindex-29, the mean score of each domain was higher in AA patients than androgenetic alopecia patients (symptoms: 27.4 vs. 27.3, functioning: 38.7 vs. 24.0, and emotions: 48.7 vs. 32.1) (Han et al, 2012).…”
supporting
confidence: 50%
See 1 more Smart Citation
“…Our results suggested that AA could affect patients' QOL more than vitiligo or androgenetic alopecia, compared with the previous studies using the similar study protocol in Korea (Bae et al, 2018;Han et al, 2012). More patients with AA have impaired QOL than patients with vitiligo (symptoms: 30.3% vs. 14.6%, functioning: 71.3% vs. 48.8%, and emotions: 81.7% vs. 65.0%) (Bae et al, 2018). For hairspecific Skindex-29, the mean score of each domain was higher in AA patients than androgenetic alopecia patients (symptoms: 27.4 vs. 27.3, functioning: 38.7 vs. 24.0, and emotions: 48.7 vs. 32.1) (Han et al, 2012).…”
supporting
confidence: 50%
“…We confirmed that AA patients have markedly impaired QOL in all aspects of symptoms, functioning, and emotions. Our results suggested that AA could affect patients' QOL more than vitiligo or androgenetic alopecia, compared with the previous studies using the similar study protocol in Korea (Bae et al, 2018;Han et al, 2012). More patients with AA have impaired QOL than patients with vitiligo (symptoms: 30.3% vs. 14.6%, functioning: 71.3% vs. 48.8%, and emotions: 81.7% vs. 65.0%) (Bae et al, 2018).…”
supporting
confidence: 47%
“…Vitiligo is a common, chronic, acquired depigmentation disorder that profoundly affects patient quality of life ; treatment is often challenging . Narrowband ultraviolet B (NBUVB) phototherapy has been the mainstay in the treatment, and 308‐nm excimer laser (EL) and other laser treatments have also been used to treat localized disease .…”
Section: Introductionmentioning
confidence: 99%
“…Pacienţii au tendinţa de a omite relatarea stresului psihologic la care sunt supuşi medicului curant, concentrându-se mai degrabă pe aspectul fizic (5). Importanţa stresului nu trebuie minimalizată deoarece poate duce la depresie, iar ulterior aceasta poate duce la ideaţie suicidală (6,7).…”
Section: Introducereunclassified